Two Autism/Dyslexia Linked Variations of DOCK4 Disrupt the Gene Function on Rac1/Rap1 Activation, Neurite Outgrowth, and Synapse Development - Huang, Miaoqi; Liang, Chunmei; Li, Shengnan; Zhang, Jifeng; Guo, Daji; Zhao, Bo; Liu, Yuyang; Peng, Yinghui; Xu, Junyu; Liu, Wei; Guo, Guoqing; Shi, Lei (Frontiers in Cellular Neuroscience, 2020)
Autism spectrum disorder (ASD) and dyslexia are both neurodevelopmental disorders with high prevalence in children. Both disorders have strong genetic basis, and share similar social communication deficits co-occurring with impairments of reading or language. However, whether these two disorders share common genetic risks remain elusive. DOCK4 (dedicator for cytokinesis 4), a guanine nucleotide exchange factor (GEF) for the small GTPase Rac1, is one of few genes that are associated with both ASD and dyslexia. Dock4 is important for neuronal development and social behaviors. Two DOCK4 variations, Exon27-52 deletion (protein product: Dock4-945VS) and a missense mutation at rs2074130 (protein product: Dock4-R853H), are associated with dyslexia and/or ASD with reading difficulties. The present study explores the molecular and cellular functions of these two DOCK4 variants on neuronal development, by comparing them with the wild-type Dock4 protein. Notably, it is revealed that both mutants of Dock4 showed decreased ability to activate not only Rac1, but also another small GTPase Rap1. Consistently, both mutants were dysfunctional for regulation of cell morphology and cytoskeleton. Using Neuro-2a cells and hippocampus neurons as models, we found that both mutants had compromised function in promoting neurite outgrowth and dendritic spine formation. Electrophysiological recordings further showed that R853H partially lost the ability to promote excitatory synaptic transmission, whereas 945VS totally lost the ability. Together, we identified R853 as a previously uncharacterized site for the regulation of the integrity of Dock4 function, and provides insights in understanding the common molecular pathophysiology of ASD and dyslexia.